KAPABILITAS PERAWAT PENDIDIK: KONSEP ANALISIS - Cicilia Ika Wulandari; Ichsan Rizany (Jurnal Ilmu Kesehatan Insan Sehat, 2026)
Introduction: The role and capabilities of nurse educators in hospitals remain unclear. Misinterpretation of these capabilities may affect the quality of teaching provided. The concept of capability has not been consistently defined for use in nursing, particularly among nurse educators. Therefore, concept clarification is needed to establish consistent theoretical and operational definitions and to guide strategies for strengthening qualified nurse educators. Objective: The purpose of this article is to conceptualize the meaning and importance of a skilled nurse educator. Methods: The design used is concept analysis. Data sources were searched from databases (Pubmed, Google Scholar, Scopus). The Walker & Avant method was applied to guide concept analysis to identify and define attributes, antecedents, and consequences. Results: Through analysis of the literature using the Walker and Avant method, three defining attributes of capability were identified: a broad multidimensional concept, specialized expertise, and continuous learning. Antecedents include readiness, support, experience, authority. The consequences of nurse educators' abilities consist of satisfaction, knowledge, self-efficacy, responsibility, optimal clinical learning. Conclusion: Capabilities are an individual’s capacity and competency to apply knowledge, attitudes, and skills to support positive learning outcomes. Ability to portray nurses as superior professional educators.